IMPLEMENTATION OF THE MODEL PREPARATION OF FUTURE TEATHERS TO THE PATRIOTIK EDUKATION OF SCHOOLBOYS MEANS UKRAINIAN MUSICAL ARTS - Г. Тупікова (Київський національний університет імені Тараса Шевченка, 2016)
This article presents a model that illustrates the relationship between the components of training future teachers to patriotic education of pupils by means of Ukrainian music and examines the results of implementation of the model.The level of formation of patriotic education of students on the cognitive-evaluative, motivational-value and actively-creative criteria on the forming stage of the experiment. The comparative analysis of the levels of patriotic education of future teachers after forming experiment. Formation of readiness of teachers to pupils by means of patriotic education of Ukrainian music was through the introduction of theoretical and practical material guidelines both in academic and extracurricular process of higher education, and implementation of the model preparing students for patriotic education of students. The positive changes in rates and levels of future teachers for these criteria. It is proved that the changes that have taken place on these criteria in some way affected by the proposed model. Done statistical verification experiment results in statistical programming environment R 3.3.0 using membrane Rstudio using Student's t test Z-test the hypothesis proportions general populations proportions in the two samples.

У статті проаналізовано результати реалізації моделі підготовки майбутніх учителів до патріотичного виховання школярів засобами українського музичного мистецтва. Досліджено рівень сформованості патріотичної вихованості студентів за когнітивно-оцінним, мотиваційно-ціннісним та діяльнісно-творчим критеріями на формуючому етапі експерименту.
РЕАЛІЗАЦІЯ МОДЕЛІ ПІДГОТОВКИ МАЙБУТНІХ УЧИТЕЛІВ ДО ПАТРІОТИЧНОГО ВИХОВАННЯ ШКОЛЯРІВ ЗАСОБАМИ УКРАЇНСЬКОГО МУЗИЧНОГО МИСТЕЦТВА
Keywords: модель; професійна підготовка; студенти; патріотичне виховання; українське музичне мистецтво; model; training; student; patriotic education; Ukrainian musical art